2020
DOI: 10.3168/jds.2019-16778
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Fate of antibiotic residues, antibiotic-resistant bacteria, and antibiotic resistance genes in US dairy manure management systems

Abstract: United States dairy operations use antibiotics (primarily β-lactams and tetracyclines) to manage bacterial diseases in dairy cattle. Antibiotic residues, antibiotic-resistant bacteria (ARB), and antibiotic resistance genes (ARG) can be found in dairy manure and may contribute to the spread of antibiotic resistance (AR). Although β-lactam residues are rarely detected in dairy manure, tetracycline residues are common and perhaps persistent. Generally, <15% of bacterial pathogen dairy manure isolates are ARB, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 196 publications
(233 reference statements)
1
73
0
2
Order By: Relevance
“…This may be due to PENG was widely used to treat infectious diseases, like cow mastitis. Oliver et al. (2020) pointed that TCs and LAs were usually used to manage bacterial disease in cows.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to PENG was widely used to treat infectious diseases, like cow mastitis. Oliver et al. (2020) pointed that TCs and LAs were usually used to manage bacterial disease in cows.…”
Section: Discussionmentioning
confidence: 99%
“…β-lactams are one of the most widely used groups of antibiotics, including in veterinary medicine [77]. β-lactam residues, β-lactam-resistant bacteria and β-lactam-resistant determinants have been found in dairy cattle manure because β-lactam antibiotics are often used to treat mastitis [14,15,40,78,79]. Pig manure can also work as a reservoir for the transferable amoxicillin antibiotic resistance genes bla TEM .…”
Section: Antibiotics and Antimicrobial Resistance Genes In Manurementioning
confidence: 99%
“…Researchers have recently ascribed the presence of antibiotic residues and antibiotic resistance bacteria in the animals' manure to be the underlying cause of increased spread of antibiotic resistance. Besides, they reported a rise in antibiotic susceptibility among dairy manure isolates of bacterial pathogens with 15% of tested bacteria to be resistant against some antibiotics [38] Most of the bacterial strains have been undergoing genetic modification for evolving resistance on account of indiscriminate and injudicious use of antibiotics for treating animal and human infections. Results of the present study demonstrate similar tendencies as all five experimental sites were shown to have been contaminated with Salmonella spp.…”
Section: Antimicrobial Resistance In Salmonella Sppmentioning
confidence: 99%